Kiribati's Strategy in Facing the Problem of Sea Level Rise through the Kiribati Adaptation Program (KAP) - Astriviany, Maurin (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2020)
The vulnerability of the Pacific Region which generally consists of small country and island nations makes countries in the region need to be aware of the threat of sea level rising. Kiribati is one of the countries that will be most affected. Therefore, the Kiribati Adaptation Program is one of the Government’s strategies that collaborated with the World Bank as the main donor party to reduce the adverse effect from sea level Rising. Divided into three phases of the program, we will see how it progresses from one phase to another. In the first phase is preparation for the program to adapt, in the second phase is the time to implement what needs to be done after reviewing the result of the first phase preparation, then in the final phase is the expansion of the program. After two phases, this third phase learned lessons from previous phases which faced few obstacles and need to be fixed before goes up to the expansion stage. Kiribati Adaptation Program will give an idea of how the strategy has been carried out by the Government of Kiribati and might become a lesson for other vulnerable countries in face the sea level rising.